2006
DOI: 10.1111/j.1445-2197.2006.03673.x
|View full text |Cite
|
Sign up to set email alerts
|

Delay to Appendicectomy and Associated Morbidity: A Retrospective Review

Abstract: Time to surgery of up to 24 h does not lead to an increase in complicated appendicitis or morbidity. When the time exceeds 24 h, there is an increased rate of complicated appendicitis and morbidity, including complications that are not directly related to the appendicitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
59
2
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(73 citation statements)
references
References 9 publications
6
59
2
6
Order By: Relevance
“…14,15 The commonly quoted perforation rate from literature in the developed world ranges from 15% to 30%. 17 Our current study, however, shows a rate of over 60%. Although this far exceeds the rates seen elsewhere in the developed world, it is similar to that from other studies from subSaharan Africa (40-50%).…”
Section: Discussionmentioning
confidence: 63%
“…14,15 The commonly quoted perforation rate from literature in the developed world ranges from 15% to 30%. 17 Our current study, however, shows a rate of over 60%. Although this far exceeds the rates seen elsewhere in the developed world, it is similar to that from other studies from subSaharan Africa (40-50%).…”
Section: Discussionmentioning
confidence: 63%
“…5 Omundsen and Dennett found that surgery for acute appendicitis up to 24 hours does not lead to an increase in morbidity but when exceeds 24 hours, the morbidity and complications increases. 6 Appendicectomy in acute appendicitis can be delayed in contrast to the earlier beliefs that complications and perforation rate increases when delayed. Delayed appendicectomy have become safe due to the parenteral antibiotics which halts the inflammation and disease progression.…”
Section: Discussionmentioning
confidence: 90%
“…2,3,[4][5][6] This is review of 283 cases of acute appendicitis undergoing appendicectomy from January 2016 to December 2016 to verify whether acute non-perforated appendicitis requires immediate surgery or can be delayed being taken up on elective basis.…”
mentioning
confidence: 99%
“…Delay in diagnosis can lead to appendiceal perforation, technical difficulties during surgery and increased morbidity [9], especially when resistant bacteria are involved, as is common in children [10]. According to the renowned teaching of Henri Mondor, surgeons are inclined to operate when the diagnosis is probable, rather than waiting until the diagnosis is certain.…”
Section: Discussionmentioning
confidence: 99%